Effects of Ca substitution on the local structure and oxide–ion behavior of layered perovskite lanthanum nickelate - Kitamura, Naoto; Kimura, Kazuki; Ishida, Naoya; Ishibashi, Chiaki; Idemoto, Yasushi (Frontiers in Materials, 2022)
La2NiO4+d-based materials with a layered perovskite structure have attracted significant attention as air-electrode materials for use in solid oxide fuel cells. In particular, Ca-substituted materials, La2-xCaxNiO4+d, have been investigated, as the partial substitution of La with Ca can improve oxide-ion conduction in the crystals. However, the local structures around the conducting oxide ion and Ca dopant are not been well understood because their distributions cannot be characterized by a general structure analysis only using Bragg peaks. Therefore, we examine the atomic structure of La1.75Ca0.25NiO4+d by a combination of molecular dynamics simulation and reverse Monte Carlo modelling using the Faber–Ziman structure factor, real-space function, and Bragg profile simultaneously. Results indicate that conducting oxide ions are introduced into rocksalt layers in the crystal and are present around La but not Ca. Furthermore, it is found that ionic diffusion is accompanied by a change in the rocksalt layer volume, which can be suppressed by partial substitution with Ca. This can be regarded as a major reason why Ca substitution improves oxide-ion diffusion in the La2NiO4+d layered perovskite.